1986
DOI: 10.1677/joe.0.1100389
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine does not attenuate phosphoinositide hydrolysis in rat anterior pituitary cells

Abstract: The hydrolysis of membrane phosphatidylinositol to yield [3H]labelled inositol phosphates by anterior pituitary cells was stimulated significantly by angiotensin II, TRH and neurotensin over a broad range of concentrations. These secretagogues also stimulated release of prolactin. Although the coincident incubation of dopamine with these agents resulted in a marked diminution of prolactin release, no concomitant reduction in inositol phosphate production was observed. In addition, bromocriptine, a potent agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…The lack of effect of acute DA administration on the basal accumulation of inositol phosphates has been previously reported [3.6, 16]. Although the inhibition of stimulated ac cumulation is controversial [3,6,16], under our experimen tal conditions, the administration of DA did not affect ei ther basal ( fig. I ) or TRH-induced accumulation of inositol phosphates.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The lack of effect of acute DA administration on the basal accumulation of inositol phosphates has been previously reported [3.6, 16]. Although the inhibition of stimulated ac cumulation is controversial [3,6,16], under our experimen tal conditions, the administration of DA did not affect ei ther basal ( fig. I ) or TRH-induced accumulation of inositol phosphates.…”
Section: Discussionsupporting
confidence: 62%
“…Acute administration of DA was reported to have no effect on the basal or stimu lated production of inositol phosphates (IPx) [3]. However, others reported that DA inhibited angiotensin I I-stimulated [6] orTRH-stimulated [16] production of IPx.…”
mentioning
confidence: 99%
“…PKC activated by phorbol esters enhances adenylate cyclase activity by inhibiting the inhibitory activity of GTP-binding Gj-protein. TRH also stimulates the cyclase activity by stimulat ing GTP-binding Gs-protein [16], It was also suggested that dopaminergic D2 receptors may be linked to the phospholipase C system by demonstrating that a brief ex posure to dopamine enhanced phosphatidyl inositol bi phosphate [17], Another group of workers proposed that the D2 receptors may be negatively coupled to the phos pholipase C system [18][19][20], but it has been difficult to demonstrate an inhibitory effect of dopamine on total inositol phosphate production [21].…”
Section: Inmentioning
confidence: 99%
“…Acute administration of DA has been shown to have no effect on either the basal or stimulated IP production in rat anterior pituitary cells [24]. However, while levels of DA (500 n M ) sufficient to elicit inhibition of prolactin release have been shown not to lower TRH-stimulated increases in intracellular IPs, higher levels such as those we have used (10 µ M ) were effective in reducing the magnitude of stimulated IP production [25]. Some laboratories have suggested that DA inhibits IP production by way of decreasing phosphoinositide-specific phospholipase C (PLC) activity [26, 27].…”
Section: Discussionmentioning
confidence: 99%